From Home to Classroom: How Parenting Styles Shape Student Participation Through Self-Efficacy - Sakineh Dehdar; S.AbdolHadi Samavi (Iranian Evolutionary Educational Psychology Journal)
Objective: The objective of the present investigation is to examine the predictive influence of parenting style on the spirit of student participation, with an emphasis on the mediating role of self-efficacy. Methods: The methodological approach employed is descriptive-correlation. The statistical population encompasses both male and female high school students in Parsian, totaling 934 individuals. Following a cluster random sampling procedure, a sample of 272 students, comprising 136 females and 136 males, was analyzed. The research instruments utilized consist of three questionnaires: the parenting styles questionnaire by Baumrind (1973), the self-efficacy scale developed by Jink and Morgan (1999), and the student participation spirit measure articulated by Anderson et al. (2019). Results: The findings derived from correlation coefficients and path analysis of the variables indicated that 1- a significant relationship exists between each of the parenting style subscales and the variables of self-efficacy and participation spirit. However, the permissive parenting style does not exhibit a significant correlation with the spirit of participation. 2- In the path analysis, it was revealed that solely the negligent parenting style fails to significantly predict the spirit of participation. Conversely, the authoritative parenting style demonstrates a positive and significant predictive capacity for the spirit of participation when mediated by self-efficacy. In contrast, the authoritarian parenting style exhibits a negative predictive influence on the spirit of participation. Conclusions: These measures are essential steps toward creating a more agile organization, as recommended for managers and officials.